$n$-selective Tsuji–Trost allylation promoted by a recyclable TSIL-palladium complex - Lledó, David; Grindlay, Guillermo; Sansano, José M. (Comptes Rendus. Chimie)
The Tsuji–Trost reaction of allylic acetates with nucleophiles is optimized using a task-specific ionic liquid (TSIL)-palladium complex in a very efficient manner. Several nucleophiles and allylic systems are studied obtaining very high yields of the corresponding products with total $n$-selectivity. The reaction is surveyed employing inexpensive allylic alcohols and 3-acyloxindole derivatives affording the expected allylated molecules after a deacylative process. The robustness of the catalytic system is assessed. The recovery and recycling of the whole catalytic system with the ionic liquid is also analyzed and the results are compared with previously reported articles in the literature.